ANALISIS KELAYAKAN PERMAINAN TRADISIONAL BOLA BEKEL SEBAGAI SUMBER BELAJAR IPA - Jiham Azzahra; Ayu Tri Ma Rifah; Alya Uzzuhroh; Khoerunnisa Aulia; Rosiana Afdila Putri; Asfiani Amalia; Aris Naeni Dwiyanti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Science learning in elementary schools often presents concepts as abstract content detached from students’ everyday experiences. The traditional game of bola bekel offers a context in which physical phenomena can be observed through an activity familiar to children. This study explores the feasibility of bola bekel as a science learning resource while also providing an avenue for introducing local culture. A descriptive study employing a survey approach involved 121 respondents, comprising teachers, education students, and prospective teachers. Responses were collected online through a semi-structured questionnaire examining science concepts, potential uses, advantages, implementation challenges, and strategies for integrating the game into instruction. The responses were reduced, categorized, and interpreted thematically. Bola bekel was perceived to contain observable phenomena related to force, motion, gravity, elasticity/ball rebound, friction, kinetic energy, and gravitational potential energy. Respondents also considered the game capable of supporting student engagement, more concrete learning experiences, and awareness of local culture. Its feasibility, however, depends on teachers’ instructional design, particularly in setting learning objectives, directing observation, managing activities, and facilitating scientific reflection. Bola bekel has the potential to be developed as a contextual, accessible, and relevant science learning resource grounded in ethnoscience for elementary education. ABSTRAK Pembelajaran IPA di sekolah dasar kerap menempatkan konsep sebagai materi abstrak yang terpisah dari pengalaman keseharian peserta didik. Permainan tradisional bola bekel menawarkan konteks yang memungkinkan fenomena fisik diamati melalui aktivitas yang telah dikenal anak. Kajian ini mengeksplorasi kelayakan bola bekel sebagai sumber belajar IPA sekaligus ruang pengenalan budaya lokal. Penelitian deskriptif dengan pendekatan survei melibatkan 121 responden yang terdiri atas guru, mahasiswa kependidikan, dan calon pendidik. Tanggapan dikumpulkan secara daring menggunakan kuesioner semi-structured yang menelaah konsep IPA, potensi pemanfaatan, kelebihan, kendala, serta strategi penerapan permainan dalam pembelajaran. Jawaban responden direduksi, dikelompokkan, lalu ditafsirkan secara tematik. Permainan bola bekel dipersepsikan memuat fenomena gaya, gerak, gravitasi, sifat elastis/pantulan bola, gaya gesek, energi kinetik, dan energi potensial gravitasi. Responden juga memandang permainan ini dapat mendukung keterlibatan siswa, pengalaman belajar yang lebih konkret, serta pengenalan budaya lokal. Kelayakannya tetap bergantung pada rancangan guru, terutama dalam menetapkan tujuan, mengarahkan pengamatan, mengelola aktivitas, dan memfasilitasi refleksi ilmiah. Bola bekel berpotensi dikembangkan sebagai sumber belajar IPA berbasis ethnoscience yang kontekstual, sederhana, dan relevan bagi pembelajaran sekolah dasar.